Sociodemographic Analysis, The Environment and The Incidence of Malaria in Siabu District, Mandailing Natal Regency - Sasmar Aurivan Harya (Pena Cendekia Insani, 2021)
Malaria is one of the infectious diseases that is still a public health problem in Indonesia, including Mandailing Natal District. The emergence of malaria is caused by various supporting factors so that the Anopheles mosquito can survive because it adapts to the existing environment. These factors are environment, then behavior, health services and heredity. The purpose of this study was to determine socio-demographic, environmental and malaria incidence in Siabu District, Mandailing Natal Regency. This research was conducted in Mandailing District, Siabu District. This research was conducted in January-April 2015. This study used a case control design. The samples of cases and controls were 31 people each. This study uses bivariate analysis with chi-square test. There is no relationship between education, work and knowledge with the incidence of malaria in Siabu District, Mandailing Natal Regency. There is a relationship between standing water and wire netting at home with the incidence of malaria in Siabu District, Mandailing Natal Regency. Communities whose house ventilation is not installed with wire screens are 7.2 times more likely to suffer from malaria than people whose houses are installed with wire screens. The presence of standing water around the house is 5.1 times more likely to suffer from malaria than people whose houses do not have stagnant water. There is a relationship between standing water and wire netting at home with the incidence of malaria in Siabu District, Mandailing Natal Regency. Communities whose house ventilation is not installed with wire screens are 7.2 times more likely to suffer from malaria than people whose houses are installed with wire screens. The presence of standing water around the house is 5.1 times more likely to suffer from malaria than people whose houses do not have stagnant water.